(untitled) (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
THE JEWISH TOWN IN KAZIMIERZ AND ITS ARCHITECTURE IN THE MID-17TH C. The article is based on an unpublished study devoted to Cracow’s Kazimierz, written by the author in 1996. It was commissioned by the “History and Culture of Jews” , a Branch of the Historical Museum of the City of Cracow. A reconstruction of the town and ownership questions in Kazimierz in the mid-17th c. is covered on the basis of written accounts from that period together with the earliest, sufficiently accurate plans, as well as the outcomes of architectural studies. This methodology allows to give a more accurate picture of the architectural layout and the function and to retrace the relationships between the status of residents and the character of residential buildings in various parts of the Jewish Town in Kazimierz to be determined. The period (the mid-17th c.) was selected to provide both an objective justification based on the spatial and cultural development of the urban organism, as well as a subjective one in the form of surviving reference sources from that period. The text presents extraordinarily rich factual material and is an excellent model text.